Metode super-ločljive optične mikroskopije - Koren, Monika (Matrika, 2019)
Three super-resolution microscopy techniques are presented. The first one allows a resolution below the diffraction limit due to fluorescence depletion by stimulated emission. It was developed on the basis of fluorescence confocal microscopy, which is also described. The second, ultra-fast absorption microscopy, is based on saturated absorption. Finally, the absorption microscopy is described, which takes advantage of nonlinearity in the transient absorption and differential illumination of the sample.
Keywords: optical microscopy; optics; optična mikroskopija; optika